Sensual Symbols and Social Confusion: Revealing the Expression of Love in 'Qoddukal Mayyās' Lyrics through Riffaterre’s Semiotic Lens - Aslama, Dhiaul Haq; Haeruddin, Haeruddin; Haeriyyah, Haeriyyah; Ramadhan, Ilham (REiLA : Journal of Research and Innovation in Language, 2025)
The increasing popularity of Arabic songs across Indonesian digital platforms has led to frequent misinterpretations, particularly when secular compositions are assumed to be religious expressions such as shalawat. This study responds to that cultural misconception by examining the lyrics of “Qoddukal Mayyās” by Mulla Uthman Al-Musili, a song often mistakenly regarded as devotional. Adopting a qualitative descriptive approach based on library research, the analysis is framed through Michael Riffaterre’s semiotic theory. The methodology involves a systematic progression through heuristic reading to identify literal meanings, hermeneutic reading to interpret symbolic and contextual layers, and the identification of matrices, models, and variants to uncover the internal structure of poetic meaning. The analysis reveals that the song articulates a deeply emotional and profane form of love, marked by symbolic imagery and figurative language. Expressions such as “your supple body,” “O my moon,” and “my heart is on fire” reflect themes of sensual longing and romantic idealization without any reference to spiritual devotion or religious content. These findings confirm that the lyrics align with the Arabic ghazal tradition, emphasizing aesthetic admiration and personal emotion rather than worship or prophetic reverence. The study contributes to the clarification of cultural misreadings in the Indonesian context and highlights the necessity for greater Arabic literary literacy. Its implications are particularly relevant for educational settings where semiotic analysis can help students and the wider public distinguish between artistic expression and religious discourse within the broader landscape of Arabic popular culture.